Measurement of J/ψ production in continuum e+e- annihilations near √s = 10.6 GeV - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Palano, A; Chen, G; Chen, J; Qi, N; et al. (2001)
The cross section σe+e- → J/ψX = 2.52 ± 0.21 ± 0.21 pb was measured. Restricting to p* > 2 GeV/c, 1.87 ± 0.10 ± 0.15 pb were found. The total cross section and the angular distribution favor the NRQCD calculation over the color singlet model.